Framing climate policy around energy independence enhances acceptance and perceived effectiveness: evidence from a Finnish survey experiment - Ahonen, Sami; Leino, Mikko; Tiihonen, Aino (Springer Science and Business Media LLC, 2025)
We investigated the impact of three justifications for implementing a road traffic emission trading system on policy acceptance and perceived effectiveness. One frame is based on increased energy independence from non-EU countries, another on potential economic benefits, and a third on ensuring efficient greenhouse gas (GHG) mitigation. The data utilized originated from an online survey experiment (n = 1504) administered in Finland in the spring of 2024. We found that the justification referring to energy independence marginally increased the acceptability of the policy, whereas the justifications appealing to potential economic benefits and effective emissions reductions did not. The energy independence frame particularly influences those who perceive climate change as a moderate risk. The results regarding perceived policy effectiveness are similar, indicating a strong association between these evaluations. It is likely that, at least in the Finnish context, the link between climate change mitigation efforts and energy independence has become more pronounced following the Russian attack on Ukraine.